Climate Comfort in Nature-Based Tourism at Tropical Region - Nofi Yendri Sudiar; Yonny Koesmaryono; . Perdinan; Hadi Susilo Arifin (Agromet, 2019)
This research reveals visitor perceptions of climate comfort in nature-based tourism areas in Indonesia. We combined a survey and modeling to calculate the comfort score based on Tourism Climate Index (TCI) and Holiday Climate Index (HCI) in three tourism sites of Ecopark Ancol, Bogor Botanical Garden, and Cibodas Botanical Garden. During the survey, we collected data on climate comfort perceptions and the role of the weather on the comfort. Totally, 793 respondents of tourism visitors participated in the study. Our results showed that almost all of visitors (>95%) stated that the weather affected the climate comfort. Interestingly, the weather condition did not influence on the decisions where the tourism site to visit. The level of perceived climate comfort for the sites were neutral (Ecopark, 57.3%), and comfortable (Bogor Botanical Garden, 60%; Cibodas Botanical Garden, 78.4%). Then by modeling we obtained the best method to calculate the comfort based on the following index: (i) TCI with Physiological Equivalent Temperature (PET) Tianjin for Ecopark (57.2), (ii) HCI for Bogor Botanical Garden (59), and (iii) HCI with PET Tianjin for Cibodas Botanical Garden (77.6). Further, perception on climate comfort was significantly difference among sex, age, and education level of the visitors. In warmer environmental condition, the older people and women feel more comfortable. Our finding revealed that topography was weak correlated with comfort perception. By understanding visitor perceptions, strategies and appropriate actions can be developed to increase comfort in the nature-based tourism industry.